Revealing the effect of decreased energy intensity of grinding in a tumbling mill during self-excitation of auto-oscillations of the intrachamber fill - Deineka, Kateryna; Naumenko, Yurii (Eastern-European Journal of Enterprise Technologies, 2019)
We have investigated a possibility to perform comparative evaluation of the effectiveness of grinding process in a tumbling mill under conventional steady and self-excited auto-oscillatory flow modes of the intrachamber fill. A mathematical model for the parameters of impact influence of the milling fill on the ground material has been constructed. We applied an analytical-experimental method to visually analyze flow patterns in the cross-section of a rotating chamber. Numerically, by using approximate procedures, we have established a dynamic effect of increasing mean sums of vertical components in impact pulses and mean sums of power of such components at self-excitation of auto-oscillations. The technological effect has been experimentally established of a significant decrease in energy intensity and a certain increase in productivity of the identified self-oscillatory grinding process, compared with the characteristics of conventional steady-state process. This involved a sieve analysis of the ground product, as well as measuring the fill flow turnover and the power of a drum rotation drive. The example considered was the process of grinding cement clinker at a degree of filling the chamber with a fill of 0.45, at a relative size of ball grinding elements of 0.026, while the gaps between grinding bodies were completely filled with the ground material. It was established that at auto-oscillation self-excitation the grinding energy intensity reduces by 27.2 %, while performance increases by 6.7 %. The effects established in this work make it possible to predict the rational parameters for aself-oscillatory process of grinding in a tumbling mill